Tanggung Jawab PT Go-Jek Indonesia terhadap Kerugian yang Diderita Pengemudi Go-Jek Melalui Fitur Go-Food - Vanda Widyawati Putri Augustti; Sunarjo Sunarjo (Jurnal Cakrawala Hukum, 2018)
Go-Jek is present in Indonesia as one of the application-based online transportation. GO-JEK Indonesia which provides various service features, one of which is Go-Food. Go-Food is a food delivery service for consumers who want certain foods in a restaurant. In practice, there are obstacles in the form of orders by irresponsible consumers with cash payments, namely fictitious orders and cancellation of orders when food has been paid by Mitra to restaurants. This study uses empirical research methods that will examine 3 (three) problems, namely the legal relationship between the parties in the Go-Food feature, GO-JEK Indonesia's responsibilities, and legal protection against the Go-Jek driver who suffered losses in terms of using features Go-Food by irresponsible consumers. In the use of the Go-Jek application, the parties are subject to an electronic partnership agreement. This agreement is classified as a standard agreement and contains several standard clauses which are prohibited by law which result in the agreement being declared null and void. So it is hoped that this research can help the parties to review the clause on the agreement made and the losses experienced by the Go-Jek driver in using the Go-Food feature by irresponsible consumers can be reduced.How to cite item: Putri Augustti, V., Sunarjo, S. (2018). Tanggung Jawab PT Go-Jek Indonesia terhadap Kerugian yang Diderita Pengemudi Go-Jek Melalui Fitur Go-Food. Jurnal Cakrawala Hukum, 9(1), 89-98. doi:https://doi.org/10.26905/idjch.v9i1.2119